Men, masculinities and violence: an ethnographic study - Ellis, Anthony (Routledge studies in crime and society, 2016)
Let's get ready to rumble -- Theorising masculinities and violence : a review -- Top lad : a violent biography -- Born to fight -- Handy lads -- It's "not me," it's "them" : violent reflections -- Shadow world -- Rolling with the punches -- References